Surgery of Eventration of the Diaphragm - hussen, waleed M.; Mohammed, Ahmed M.; Yuser, Akeel S. (Journal of the Faculty of Medicine Baghdad, 2021)
AbstractBackground: Eventration of diaphragm is an abnormal elevation of the diaphragm. Publishing on eventration of diaphragm in Iraq is scarce.Objective: This study was carried out to report on the Iraqi experience on eventration of diaphragm.Methods: A total of 18 patients with eventration diaphragm were included in this study. A review of case records of patients with eventration diaphragm treated in Ibn Al-Nafees Teaching Hospital was done. Review of records took place for the period of March 2012 to Dec. 2017.Results: The age of patients was ranged 5 months to 70 years, giving male to female ratio of 2:1. Dyspnea was dominating presenting symptoms followed by cough. The left hemidiaphragm was the most affected site (83.3%). The cause of eventration of diaphragm was idiopathic in 72.2% of patients. Chest X ray showed the elevation of the affected hemidiaphragm. CT scan demonstrated the thinned-out raised hemidiaphragm. The most common complications were atelectasis, and recurrent chest infection. Hospital stay was ranging 4-14 days.Conclusion: Eventration of diaphragm is not uncommon in Iraq. Presentation, management, and complication are similar to that reported in global centers.  Key words:  Diaphragm. Eventration.  Plication. Surgical repair. Phrenic nerve injury